2021
DOI: 10.1093/ajcn/nqab145
|View full text |Cite
|
Sign up to set email alerts
|

Healthy dietary patterns and common pregnancy complications: a prospective and longitudinal study

Abstract: Background Adherence to alternate Healthy Eating Index (AHEI), alternate Mediterranean diet (AMED), and Dietary Approaches to Stop Hypertension (DASH) has been linked to lower risks of chronic diseases. However, their associations with common pregnancy complications are unclear. Objectives This study investigates the associations of AHEI, AMED, and DASH during periconception and pregnancy with common pregnancy complication ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 42 publications
2
43
0
6
Order By: Relevance
“…Systematic reviews have shown promising results in promoting adequate GWG and glycemic control by following nutrition and lifestyle recommendations during pregnancy [ 7 , 8 ]. In addition, observational studies have reported positive results in preventing hypertensive disorders, low birth weight, and preterm birth in women with better diet quality indices compared to women with lower dietary quality scores [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews have shown promising results in promoting adequate GWG and glycemic control by following nutrition and lifestyle recommendations during pregnancy [ 7 , 8 ]. In addition, observational studies have reported positive results in preventing hypertensive disorders, low birth weight, and preterm birth in women with better diet quality indices compared to women with lower dietary quality scores [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings add to the growing body of evidence demonstrating that the Mediterranean diet pattern may play an important role in preserving the health of women across the lifespan, including during pregnancy. 10,[12][13][14] Long-term intervention studies are needed to assess whether promoting a Mediterranean-style diet pattern around the time of conception and throughout pregnancy can prevent APOs or reduce their downstream associations with future CVD risk. This may be particularly useful to study in pregnant persons at high risk for APOs.…”
Section: Discussionmentioning
confidence: 99%
“…Eating patterns before and during pregnancy characterized by a high intake of fruits, vegetables, legumes, whole grains, nuts, olive oil, and a low intake of red meat and processed meats have been associated with an increased risk of hypertension during pregnancy. Although the biological mechanisms by which MD plays a protective role are not precisely known, these findings could indicate that the consumption of unsaturated fatty acids and micronutrients as well as some bioactive compounds make this diet help prevent complications during pregnancy ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the beneficial effects of the MD, some authors highlight the need to recover the MD pattern in the general population and, in particular, in pregnant women, to avoid overweight and obesity, problems during pregnancy, as well as to achieve an adequate weight gain, as all this is related to overweight and the increase in adiposity in the offspring ( 40 , 41 , 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%